Enhanced photocatalytic degradation of 2-methyl-4-chlorophenoxyacetic acid (MCPA) by the addition of H2O2. (July 2021) - Kelly, Jamie; McDonnell, Cíara; Skillen, Nathan; Manesiotis, Panagiotis; Robertson, Peter K.J.
Abstract: Photocatalytic remediation technology has been shown to be a favorable approach for the removal of a range of environmental pollutants in water treatment. While this approach can often achieve complete degradation, often overlooked are reaction intermediates that are potentially as harmful as the original parent compound. In the case of photocatalytic oxidation of the herbicide 2-methyl-4-chlorophenoxyacetic acid (MCPA), we have recently shown that 4-chloro-2-methylphenol (CMP) is formed as the primary intermediate. To ensure the continued development of the technology, it is crucial to ensure the removal of both MCPA and CMP can be achieved by photocatalysis. Reported here is the enhanced photocatalytic removal and subsequent suppression of MCPA and CMP respectively, by the addition of small quantities of H2 O2 . While the addition of H2 O2 often accelerates degradation rates ( via increased OH radical production), it was found to restrict the formation of CMP in this study through competitive adsorption at the surface of TiO2 . Based on the combination of MCPA removal coupled with supressed CMP formation, 0.5% H2 O2 was determined to be an optimal loading for the process. Under these conditions 100% MCPA removal was achieved (to the limit of HPLC detection) after 45 min irradiation at a degradation rate of ∼1 mg L −1 min −1 (ƞphoton  = 4.4), which also resulted in a ∼83% reduction in CMP formation when compared to a system with no H2 O2 present. Highlights: First report of use of hydrogen peroxide to enhance the photocatalytic decomposition of MCPA. H2 O2 found to inhibit the generation of the degradation by-product CMP. Complete removal of MCP and CMP achieved within 90 min photocatalysis. Optimum removal of MCPA achieved using loading of 0.5% H2 O2 .